2005
DOI: 10.1084/jem.20050176
|View full text |Cite
|
Sign up to set email alerts
|

CD28 costimulatory signal induces protein arginine methylation in T cells

Abstract: Protein phosphorylation initiates signal transduction that triggers lymphocyte activation. However, other posttranslational modifications may contribute to this process. Here, we show that CD28 engagement induced protein arginine methyltransferase activity and methylation on arginine of several proteins, including Vav1. Methylation of Vav1 and IL-2 production were reduced by inhibiting S-adenosyl-L-homocysteine hydrolase, an enzyme that regulates cellular transmethylation. Methylated Vav1 was induced in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 24 publications
5
89
1
Order By: Relevance
“…Several labs including our own have also reported that CD28 ligation in the absence of TCR engagement can activate NFAT and NFkB activity as well as protein arginine methylation. 88,89,92,118,119 CD28 has long been found to preferentially activate JNK and NFkB, an event that may be accompanied by a unique outcome such as TH2 differentiation. Similarly, P3K activation of numerous PH-domain carrying proteins would cooperate with aspects of TCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Several labs including our own have also reported that CD28 ligation in the absence of TCR engagement can activate NFAT and NFkB activity as well as protein arginine methylation. 88,89,92,118,119 CD28 has long been found to preferentially activate JNK and NFkB, an event that may be accompanied by a unique outcome such as TH2 differentiation. Similarly, P3K activation of numerous PH-domain carrying proteins would cooperate with aspects of TCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These complexes cooperate with ribosomes assembly chaperone (Rac) signaling pathway downstream effector of Vav and the mitogen-activated kinase kinase 1 (MEKK1), a kinase known to regulate the c-jun N-terminal kinase (JNK) pathway, regulates both NF-κB and the activator protein 1 (AP-1), which controls cytokine secretion (43,45,46). Moreover, Vav-1 plays a key role in the control of NF-κB pathway by targeting IKKα in the T cell membrane and favoring its activation in response to CD28 stimulation (47), which increases protein arginine methyltransferase activity and subsequently promotes the methylation on arginine residues of Vav1 (48). It is also shown that PKC isotypes are not dispensable in the signaling pathway of cytokine production induced by CD28, which recruits PKCθ in immunological synapse and enhances nuclear factor of activated T cells (NF-AT), AP1 translocation that mediates IL-2 secretion (49).…”
Section: Intracellular Signals Of Costimulation In T Cell Responsementioning
confidence: 99%
“…53 To confirm that MTA exerted indeed an impact on global asymmetric methylation events, stimulated T cells were lysed after distinct periods of time and a Western blot was performed to detect global asymmetric protein methylation. Fig.…”
Section: Mechanism Of T Cell Inhibitionmentioning
confidence: 99%